PERAN PEMERINTAH KABUPATEN KAMPAR DALAM PENGEMBANGAN PERPUSTAKAAN DESA TAHUN 2018-2020 - Muhammad Muhyidin; Wan Asrida (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2022)
Each district only has a few villages that have a village library, and it is rare for a village that has a village library to have complete facilities as well as adequate books and services, and most libraries in the village are only for building displays. Riau Province. In the Regent's Regulation Number 55 of 2016 concerning the Job Description of the Kampar Regency Library and Archives Service in article 6,